(Diphenylphosphino)alkyl-functionalized nucleophilic carbene complexes of palladium - Tsoureas, Nikolaos; Danopoulos, Andreas A.; Tulloch, Arran A.D.; Light, Mark E. (Organometallics, 2003)
The (diphenylphosphino)alkyl-functionalized nucleophilic heterocyclic carbene (NHC) complexes of palladium LPdX2 (L = (3-R1)[1-Ph2P(CH2)2]-imidazol-2-ylid ene; R1 = 2,6-Pr2iC6H3, 2,4,6-Me3C6H2; X = CH3 (3a,b), X = Br (4a,b)) have been synthesized by the reaction of the in situ generated functionalized NHC ligand La or Lb with Pd(tmed)(CH3)2 and Pd(COD)Br2, respectively, and structurally characterized. Interaction of 3a with H(Et2O)- {B[3,5-(CF3)2C6H2]4} and pyridine or with (CF3)2CHOH and pyridine in CH2Cl2 gave the monocationic complexes [(La)Pd(CH3)(pyridine)]+(A)- (A- = {B[(3,5-CF3)2C6H2]4}-, (CF3)2CHO-); acetonitrile and benzonitrile analogues can be prepared in an analogous way. Reaction of 4a with AgBF4 in MeCN gave the dicationic complexes [(La)Pd(MeCN)2](BF4)2. Complexes 3 show moderate catalytic activity for the coupling of acrylates with aryl bromides but not chlorides. The cationic species generated in situ from 3a and H(Et2O){B[(3,5-CF3) 2C6H2]4} in CH2Cl2 under CO/ethylene acts as a copolymerization catalyst under mild conditions.